2011
DOI: 10.1371/journal.pone.0021041
|View full text |Cite
|
Sign up to set email alerts
|

The Definition of Insulin Resistance Using HOMA-IR for Americans of Mexican Descent Using Machine Learning

Abstract: ObjectiveThe lack of standardized reference range for the homeostasis model assessment-estimated insulin resistance (HOMA-IR) index has limited its clinical application. This study defines the reference range of HOMA-IR index in an adult Hispanic population based with machine learning methods.MethodsThis study investigated a Hispanic population of 1854 adults, randomly selected on the basis of 2000 Census tract data in the city of Brownsville, Cameron County. Machine learning methods, support vector machine (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
131
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 11 publications
8
131
1
2
Order By: Relevance
“…The cutoff value is different for different population like one large study study comprising of Hispanic population of 1854 adults concluded that cutoff value of HOMA-IR was 3.80. This value was far greater than popular clinical cutoff value of 2.6 (19) . If various limitations of HOMA-IR values and factors affecting its cut-off values in different population is kept in mind then it's one of the most reliable, less invasive, inexpensive, and less labor-intensive method to measure insulin resistance (20) .…”
Section: Discussionmentioning
confidence: 66%
“…The cutoff value is different for different population like one large study study comprising of Hispanic population of 1854 adults concluded that cutoff value of HOMA-IR was 3.80. This value was far greater than popular clinical cutoff value of 2.6 (19) . If various limitations of HOMA-IR values and factors affecting its cut-off values in different population is kept in mind then it's one of the most reliable, less invasive, inexpensive, and less labor-intensive method to measure insulin resistance (20) .…”
Section: Discussionmentioning
confidence: 66%
“…The higher value reported for HOMA-IR (2.5), compared with those found in this study means that lower ROC curves (1.87 women, 1.55 men) could be explained by two facts: first, the detection of MetS in different ages (children or young), and second, in our study the young with one or two metabolic alterations were included in the 'Non-Healthy' group. In other study [14], using a machine learning algorithm involving several parameters related to MetS, including among them the serum aminotransferases, proposed a HOMA-IR cut-off point of 2.6 (and hence with 83% sensitivity, 54% specificity) for Americans of Mexican ascent. Furthermore, in one study [15] based on a sample population of 22 Japanese of 22-24 years old, set an upper threshold of 2.5 for HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…MK Garg et al (46) also concluded that waist hip ratio was negatively associated with insulin sensitivity and positively associated with insulin resistance which were statistically significant. Hui-Qi Qu et al (52) also concluded that insulin resistance was positively correlated with waist hip ratio. Waist hip ratio contributes an additional independent effect, which emphasizes the important role of central fat distribution in the risk of insulin resistance (52) .…”
Section: Hip Circumference (Cms)mentioning
confidence: 97%
“…Hui-Qi Qu et al (52) also concluded that insulin resistance was positively correlated with waist hip ratio. Waist hip ratio contributes an additional independent effect, which emphasizes the important role of central fat distribution in the risk of insulin resistance (52) . Otto Tschritter, MD et al (53) concluded that waist hip ratio was more in…”
Section: Hip Circumference (Cms)mentioning
confidence: 97%